Pediatric Orthopedics in Practice - Hefti, Fritz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book communicates the latest findings in pediatric orthopedics and answers key everyday questions in the field in an informative, readily understandable manner. The scope is comprehensive, encompassing all aspects of diagnosis and therapy. After an opening section on basic principles, the two main sections discuss diseases and injuries by site and cover systemic conditions including trauma, infections, juvenile rheumatoid arthritis, tumors, and hereditary diseases. The book is the translation of the latest edition of the well-known classic Kinderorthopädie in der Praxis, which presents the collected knowledge of experts from Basel University Children's Hospital – Fritz Hefti and his co-workers Reinald Brunner, Carol Claudius Hasler, and Gernot Jundt. This edition has been revised and updated in a variety of ways. New findings are incorporated into all chapters, important advances in treatment are presented, and the latest concepts in tumor diagnosis and neuro-orthopedics are discussed. The book contains more than 150 additional illustrations, including new clinical images and radiographs and many further amusing cartoons by Franz Freuler. The aim is to make children’s orthopedics fun – in both practice and theory! The book has received several awards.
Basic Principles: General -- Diagnosis -- Development of the musculoskeletal system. Diseases and injuries by site: Spine, trunk -- Pelvis, hips and thighs -- Knee and lower leg -- Foot and ankle -- Upper extremities. Systematic aspects of musculo-skeletal disorders: Traumatology - basic principles -- Axes and lengths -- Infections -- Juvenile rheumatoid arthritis -- Tumors -- Hereditary diseases -- Neuro-orthopaedics.
Keywords: Orthopedics; Pediatrics; Physiotherapy; Orthopedics; Pediatrics; Physiotherapy